ISOLASI BAKTERI PENGHASIL SELULOSA DARI BUAH-BUAHAN DIPASAR TRADISIONAL MAKASSAR - Herwin Herwin; Fitriana Fitriana; Ayyub Harly Nurung (Fakultas Farmasi UMI, 2020)
Isolation of bacterial cellulose from fruits in traditional market of Makassar have been done. The objective of this research is to adding diversity of microorganism that can producing cellulose and observe it’s both optimum temperature and pH. First step is isolation of bacteria from Watermelon, Papaya, Cantaloupe, Mango, Dragon fruit, and Banana that found in traditional market in Makassar using Hestrin-Schramm (HS) agar. Each colony bacteria have been separated to making pure culture using HS agar then the colony was screening in HS broth to obtain colony bacteria that producing cellulose. Screening test found that 10 isolate that can produce cellulose which is MB-B02, MS-B01, MS-B03, NB-B03, PB-B01, PB-B02, PB-B03, PB-B04, PS-B01, and PS-B03. Then the colony that producing cellulose was optimize its temperature and pH. Cellulose obtained from optimization was measure it’s weight to determine optimum temperature and pH. Based from optimization found that 250C was optimum temperature for MS-B01, MS-B03, NB-B03, dan PB-B04, and 370 was optimum temperature for MB-B02, PB-B01, PB-B03, PS-B01, dan PS-B03, meanwhile for isolate PB-B02 optimum both in 250C dan 370C dan pH optimum for all isolate is pH 6